PENGARUH KREATIVITAS DAN INOVASI TERHADAP KEPUASAN KERJA KARYAWAN MNC ANIMASI - Yollanda Dwi Sagita; Amanda Setiorini (Jurnal Ekonomi dan Industri, 2022)
The purpose of this study was to determine the effect of creativity and innovation on job satisfaction of PT. MNC Animation. This research was conducted on 68 respondents to employees of PT. MNC Animation in Jakarta. Obtaining data results using a questionnaire with a differential semantic scale. The analysis technique uses multiple and simple linear regression. Based on the test results found that creativity and innovation simultaneously have a significant effect on employee job satisfaction. In contrast to creativity which does not have a partial effect. However, innovation has an effect on job satisfaction partially.